THE EFFECT OF THE COOPERATIVE INTEGRATION METHOD OF FRAGMENTED INFORMATION USING THE JUMPING DEFENSIVE WALL DEVICE (JWD) IN TEACHING THE FRONT SHOT AND THE LAY-UP SHOT IN BASKETBALL FOR STUDENTS - Asst. Prof. Dr. Waleed Sameer Hadi (Proximus Journal Publishing, 2025)
Progress in the teaching process requires instructors to select the best methods to improve shooting skills, which are of great importance in basketball. However, the significance of this study lies in the absence of a similar device
Keywords: Defensive Wall Device; Cooperative Integration Method of Fragmented Information; Types of Shooting)